Microscopic evaluation of the ventricular tissue using stereological and Voronoi tessellation methods: Application on doxorubicin-induced cardiotoxicity in rats. (October 2017) - Rafati, Ali; Jafarinezhad, Zahra; Karbalay-Doust, Saied; Hosseini, Leila; Noorafshan, Ali
Highlights: Pair- and cross-correlation functions show doxorubicin induces disarrangement and dispersion of the myocardium and vessel. Voronoi tessellations shows abnormal territories for myocardium and vessel in the cardiotoxicity. Abstract: There is limited quantitative microscopic information concerning the three-dimensional arrangement of cardiomyocytes and microvessels in cardiotoxic condition. The aim of this study was to evaluate the cardiac tissue of rats under different experimental conditions using modern second-order stereology and Voronoi tessellation techniques to show the spatial arrangement of the cardiomyocytes and microvessels. Sprague-Dawley rats were randomly divided into two groups (n = 6). The control group received PBS and the doxorubicin (DOX) group received 4 mg/kg DOX on days 1, 8, 15, and 22. On the 24th day, the left ventricle was sectioned and prepared according to the "orientator" method for microscopically evaluations. The "covariance functions" were plotted using "linear dipole probes". Polygonal tessellation of the ventricles was also diagrammed using ImageJ software. The plotting the covariance curves of the cardiomyocytes and microvessels forming the "gaps" by slopped down, crossing the reference line and rose again. In the control group, the gaps were placed at 35–40 μm and 14–16 μm for the cardiomyocytes and microvessels, respectively. In the cardiotoxic group, the curves demonstrated larger gaps in comparison with the normal hearts, indicating repulsion of these structures. The curves of the cross-correlation function of the cardiomyocytes-microvessels also demonstrated the cardiomyocytes and microvessels were not normally correlated after the toxicity. Evaluation of Voronoi tessellations for the cardiomyocytes nuclei and microvessels in the normal and cardiotoxic groups showed that the areas of polygons in the normal heart were placed in the smaller range, while the areas fell in a larger range in the cases of cardiotoxicity. Stereological and Voronoi Tessellation methods showed that ventricular tissue lost its normal spatial arrangement in doxorubicin-induced cardiotoxicity in rats.